Pengaruh kepemimpinan, pengambilan risiko, inovasi, partisipasi intensif dan partisipasi kontributif terhadap kinerja koperasi di Purbalingga Jawa Tengah - Ambarriani, Anastasia Susty (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the effect of leadership, risk taking, innovation, intensive participation and contributive participation on the performance of cooperatives in Banyumas, Central Java. The method used is multiple regression analysis using the F-test, R2-test, and T-test analysis methods. Based on the results of the analysis and discussion, it shows that risk-taking, innovation, and intensive participation affect the performance of cooperatives in Purbalingga, Central Java, Indonesia. Contributive leadership and participation have no effect on cooperative performance in Purbalingga, Central Java, Indonesia.